Transport of Anions across the Dialytic Membrane Induced by Complexation toward Dendritic Receptors - Cuřínová, Petra; Winkler, Maximilian; Krupková, Alena; Císařová, Ivana; Budka, Jan; Wun, Chang Nga; Blechta, Vratislav; Malý, Marek; Červenková Št'astná, Lucie; Sýkora, Jan; Strašák, Tomáš (ACS omega, 2021)
A novel approach to inducing anion transport over the dialytic membrane was proposed and successfully tested using the dihydrogen phosphate anion. The anion receptor based on isophthalamide was anchored on a dendritic skeleton, resulting in a macromolecular structure with a limited possibility to cross the dialytic membrane. The dendritic receptor was placed in a compartment separated from a mother anion solution by a membrane. The resulting anion complexation reduced the actual concentration of the anion and induced the anion transfer across the membrane. The anion concentration in mother solution decreased, while it was found to be increased in the compartment with the dendritic receptor. This phenomenon was observed using dendritic receptors with four and eight complexation sites. A detailed analysis of a series of dialytic experiments by 1H NMR spectroscopy enabled an assessment of the complexation behavior of both receptors and an evaluation of the dendritic effect on the anion complexation.